Studies of Dijet Transverse Momentum Balance and Pseudorapidity Distributions in Ppb Collisions at ?snn= 5.02 Tev - CMS Collaboration; Karapınar, Güler; Karapınar, Güler (Springer Verlag, 2014)
Dijet production has been measured in pPb collisions at a nucleon–nucleon centre-of-mass energy of 5.02 TeV. A data sample corresponding to an integrated luminosity of 35 nb−1was collected using the Compact Muon Solenoid detector at the Large Hadron Collider. The dijet transverse momentum balance, azimuthal angle correlations, and pseudorapidity distributions are studied as a function of the transverse energy in the forward calorimeters (E4<|η|<5.2 T). For pPb collisions, the dijet transverse momentum ratio and the width of the distribution of dijet azimuthal angle difference are comparable to the same quantities obtained from a simulated pp reference and insensitive to E4<|η|<5.2 T. In contrast, the mean value of the dijet pseudorapidity is found to change monotonically with increasing E4<|η|<5.2 T, indicating a correlation between the energy emitted at large pseudorapidity and the longitudinal motion of the dijet frame. The pseudorapidity distribution of the dijet system in minimum bias pPb collisions is compared with next-to-leading-order perturbative QCD predictions obtained from both nucleon and nuclear parton distribution functions, and the data more closely match the latter. © 2014, CERN for the benefit of the CMS collaboration 2014.
Keywords: Dijet; Transverse momentum; Quantum Chromodynamics (QCD); High energy physics